(Multi)letramentos, leitura e interpretação do gênero charge: contribuição para formação do leitor proficiente - Siqueira, Romildo (2023)
This research has as its theme Literacies: reading, interpretation and writing of multimodal texts in high school from the perspective of (multi)literacies and their contribution to the formation of proficient readers. It is limited to the practice of reading, interpreting and producing texts of multimodal genres, based on the latest external assessments (SAEB; ENEM) of the curricular components of the Portuguese language. The general objective is to analyze contributions provided by reading practices of the discursive genre cartoon, developed through the application of the (multi)literacies approach. The theoretical frameworks used are articulated by studies by Bakhtin (2016) and Fiorin (2008), in relation to discursive genres as a form of social interaction between subjects and expansion of the sociocultural repertoire; Petit (2009, 2013), Kalantzis, Cope and Pinheiro (2020), Rojo (2012, 2013, 2015), Coscarelli (2002, 2016) regarding reading, reading comprehension, multimodality and (multi)literacies; Kress (2000), Coscarelli and Ribeiro (2017) and Ribeiro (2017, 2021) regarding multimodal reading and digital technological contributions in reading practices, considering the need for a multiliterate view of students. The corpus of analysis covers a semi-structured diagnostic questionnaire on reading and knowledge of the discursive genre cartoon and three cartoons from the Enem review notebook (Agoravaienem) and material available in virtual media: cartoon composed exclusively of non-verbal elements, cartoon of correlation between the verbal and non-verbal materiality and charge in which the verbal element overlaps the non-verbal. As for the methodology, it is an exploratory, bibliographical and documentary research with a qualitative approach developed through action research carried out in a class of the 3rd year of high school, of a public school, in the city of Pimenta Bueno (RO). This research encourages the development of pedagogical practices aimed at consolidating abilities to read, analyze and reflect on meanings constructed by multimodal genres. As a result, we emphasize that reading, interpretation and writing practices involving the multimodal charge discursive genre expand sociocultural knowledge, increase proficiency and promote the (multi)literacies of the reader and high school student today, in order to provide autonomy, criticality and positioning as a social agent